Parents' knowledge, awareness and attitudes of cord blood donation and banking options: an integrative review - Lisa Peberdy; Jeanine Young; Debbie Louise Massey; Lauren Kearney (BMC, 2018)
Abstract Background For over 25 years cord blood has been used as an alternative to bone marrow for therapeutic use in conditions of the blood, immune system and metabolic disorders. Parents can decide if they would like to privately store their infant's cord blood for later use if needed or to publicly donate it. Parents need to be aware of the options that exist for their infant's cord blood and have access to the relevant information to inform their choice. The aim of this paper is to identify parent's knowledge and awareness of cord blood donation, private banking options and stem cell use, and parent sources and preferred sources of this information. Methods An integrative review was conducted using several electronic databases to identify papers on parents' knowledge, attitudes and attitudes towards umbilical cord blood donation and banking. The CASP tool was used to determine validity and quality of the studies included in the review. Results The search of the international literature identified 25 papers which met review inclusion criteria. This integrative review identified parents' knowledge of cord banking and/or donation as low, with awareness of cord blood banking options greater than knowledge. Parents were found to have positive attitudes towards cord blood donation including awareness of the value of cord blood and its uses, with the option considered to be an ethical and altruistic choice. Knowledge on cord blood use were mixed; many studies' participants did not correctly identify uses. Information sources for parents on cord blood was found to be varied, fragmented and inconsistent. Health professionals were identified as the preferred source of information on cord blood banking for parents. Conclusions This integrative review has identified that further research should focus on identifying information that expectant parents require to assist them to make informed choices around cord blood banking; and identifying barriers present for health professionals providing evidence based information on cord blood use and banking options.